What's Happening in AJE (2003-2004) - Lori Wingate (The Evaluation Center at Western Michigan University, 2004)
The article analyzes articles published in the American Journal of Evaluation, developing categories for articles focused on evaluation practice, methods, theory, metatheory, and history.